Analisa Efektifitas Keberlangsungan Kegiatan Bisnis UMKM Epok-Epok Ana - Asri, Dhita Hafizha; Eviyani, Estin Rose; Yeronica, Fernanda; Risvi, Hellena; Melissa; Elzagi, Verliana; Febiana, Anjela Rini (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Epok-Epok Ana is one of the well-known epok-epok businesses in Batam City, especially in the bengkong area. Selling epoks that taste good and at affordable prices is one way to reach lower-class customers. Even though they accept orders by phone, Epok-Epok Ana still requires customers to make their own purchases because delivery services are not yet offered. This paper aims to analyze the effectiveness of the sustainability of Epok-Epok Ana's MSME business activities. The method used in collecting information is through interviews and data processing and analysis methods are displayed descriptively and quantitatively. The results of this paper include a business analysis that identifies MSME combining resources, six basic rights of existing and suggested consumers for MSMEs, Epok-Epok Ana's marketing strategy through social media, and key motivation analysis to produce recommendations that can improve product and service quality. at Epok-Epok Ana Batam